The Effects of Transcranial Direct Current Stimulation (tDCS) on Balance Control in Older Adults: A Systematic Review and Meta-Analysis - Guo, Zhenxiang; Bao, Dapeng; Manor, Brad; Zhou, Junhong (Frontiers in Aging Neuroscience, 2020)
Background: Recently, considerable research has been conducted to study the effects of transcranial direct current stimulation (tDCS) on balance control in older adults. We completed a comprehensive systematic review and meta-analysis to assess the efficacy of tDCS on balance control in this population. Methods: A search strategy based on the PICOS principle was used to find the literatures in the databases of PubMed, EMBASE, EBSCO, Web of Science. The quality and risk of bias in the studies were independently assessed by two researchers. Results: Ten studies were included in the systematic review. A meta-analysis was completed on six of these 10, with a total of 280 participants. As compared to sham (i.e., control), tDCS induced significant improvement with low heterogeneity in balance control in older adults. Specifically, tDCS induced large effects on the performance of the timed-up-and-go test, the Berg balance scale, and standing postural sway (e.g., sway area) and gait (e.g., walking speed) in dual task conditions (standardized mean differences (SMDs) =-0.99~3.41 95% confidence limits (CL): –1.52~4.50, p<0.006, I2<52%). Moderate-to-large effects of tDCS were also observed in the standing posture on a static or movable platform (SMDs =0.37~1.12 95%CL: -0.09~1.62, p<0.03, I2<62%). Conclusion: Our analysis indicates that tDCS holds promise to promote balance in older adults. These results warrant future studies of larger sample size and rigorous study design and results report, as well as specific research to establish the relationship between the parameter of tDCS and the extent of tDCS-induced improvement in balance control in older adults.